Analysis of Factors Influencing the Implementation of Occupational Safety and Health (OSH) in the Electric Power Transmission Sector Using a Structural Equation Modeling Approach - Ardian Pradipta; Retno Widyaningrum (Journal of Social Research, 2026)
Occupational Safety and Health (OSH) implementation in the electricity transmission sector remains a critical issue due to the high level of workplace risks, including electrical hazards, work at heights, and dynamic field conditions. Strengthening OSH practices requires an understanding of the factors influencing workers’ safety behavior. This study aims to identify and examine the factors affecting OSH implementation in the electricity transmission sector by analyzing the relationships among safety knowledge, safety culture, safety leadership, safety attitude, and safety citizenship behavior. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 125 employees and outsourced personnel within the transmission management unit of PT PLN (Persero). The research model was evaluated through measurement model and structural model assessments, including validity, reliability, coefficient of determination (R²), predictive relevance (Q²), effect size, goodness-of-fit evaluation, and hypothesis testing using bootstrapping analysis. The results indicate that seven out of the eight proposed hypotheses were supported. Safety knowledge, safety leadership, and safety attitude significantly influenced safety citizenship behavior, with safety leadership demonstrating the strongest effect on safety culture (? = 0.575), and safety attitude significantly affecting safety citizenship behavior (? = 0.544). However, safety culture did not significantly influence safety attitude. The findings highlight that improving OSH implementation requires strengthening safety leadership, enhancing safety knowledge, and developing positive safety attitudes among workers. This study provides strategic recommendations for improving safety programs and supporting the achievement of zero accidents in the electricity transmission sector.